A more powerful familywise error control procedure for evaluating mean equivalence. Issue 11 (1st November 2020) - Davidson, Heather; Cribbie, Robert A.
Abstract: When one wishes to show no meaningful differences among group means, equivalence tests should be used, as a nonsignificant test of mean difference does not provide evidence supporting equivalence. This research proposes two modified stepwise procedures for controlling the familywise Type I error rate, based on the Bonferroni-type correction of k 2 /4 (where k is the number of groups to be compared) proposed by Caffo, Lauzon and Rohmel (2013 Correction to "easy multiplicity control in equivalence testing using two One-Sided tests. The American Statistician 67 (2):115–6) Bonferroni-type correction of k 2 /4 (where k is the number of groups to be compared). Using a Monte Carlo simulation method, we show that adopting a stepwise procedure increases power, while maintaining the familywise error rate at or below α . Implications for applied research and directions for future study are discussed.